2007
DOI: 10.1515/znc-2007-11-1217
|View full text |Cite
|
Sign up to set email alerts
|

A Semisynthetic 5-n-Alkylresorcinol Derivative and its Effect upon Biomembrane Properties

Abstract: MSAR (1-sulfate-3-myristoyl-5-pentadecylbenzene) is a semisynthetic derivative of 5-npentadecylresorcinol (C15:0). MSAR exhibits hemolytic activity against sheep erythrocytes with a EH 50 value of (35 ð 1.7) μm. At low concentrations MSAR also exhibits the ability to protect cells against their hypoosmotic lysis. This protective effect is significant as, at 0.1 μm of MSAR, the extent of osmotically induced cell lysis is reduced by approx. 20%. It was demonstrated that the 9-anthroyloxystearic acid signal was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Resorcinolic lipids from rye bran and cardol from CNSL affected the properties of the hydrophobic region of the bilayer, but the properties of the subsurface part of the phospholipid bilayer were altered by anacardic acid, methylocardol, alkylphenol [21], and merulinic acid [41]. It was also found that 1-sulfate-3-myristoyl-5-pentadecylbenzene, a semisynthetic derivative of 5-npentadecylresorcinol, intensively quenched the 9-anthroyloxystearic acid signal, which suggests a relatively deep location of these molecules within the lipid bilayer [23]. Similar properties were also shown for cardanol (Stasiuk, unpublished data).…”
Section: Phenolic Lipids Interact With Biological Membranes and Modelmentioning
confidence: 96%
See 2 more Smart Citations
“…Resorcinolic lipids from rye bran and cardol from CNSL affected the properties of the hydrophobic region of the bilayer, but the properties of the subsurface part of the phospholipid bilayer were altered by anacardic acid, methylocardol, alkylphenol [21], and merulinic acid [41]. It was also found that 1-sulfate-3-myristoyl-5-pentadecylbenzene, a semisynthetic derivative of 5-npentadecylresorcinol, intensively quenched the 9-anthroyloxystearic acid signal, which suggests a relatively deep location of these molecules within the lipid bilayer [23]. Similar properties were also shown for cardanol (Stasiuk, unpublished data).…”
Section: Phenolic Lipids Interact With Biological Membranes and Modelmentioning
confidence: 96%
“…It was demonstrated that 1-sulfate-3-myristoyl-5-pentadecylbenzene (pentadecylresorcinol derivative) is a more hydrophilic compound, with a CMC value of 0.893 lM [23]. A micellization study of 2,4-sodium dissulfonate-5-npentadecylphenol synthesized from hydrogenated cardanol showed that the CMC depends on temperature and electrolyte (potassium chloride) concentration in the subhase buffer and that it decreased with increasing electrolyte concentration and temperature.…”
Section: Amphiphilic Properties Of Phenolic Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Como se mencionó anteriormente, los AR poseen una gran afinidad con bicapas lípidicas (i.e., membranas celulares), interactuando con fosfolípi-dos mediante puentes de hidrógeno (Stasiuk et al, 2007) aumentando la permeabilidad de la membrana cuando ésta se encuentra en un medio acuoso rico en 5-n-alquilresorcinoles. Cuando estos compuestos son incorporados en la bicapa durante su formación, los liposomas resultantes son más eficaces encapsulando y preservando solutos solubles en agua, que cuando no se encuentran AR en el medio (Gubernator et al, 1999; Stasiuk y Kozubek, 2010).…”
Section: Propuestas Reportadas De Mecanismos De Acción De Arunclassified